2000
DOI: 10.1007/s002619910044
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder carcinoma: color Doppler sonography

Abstract: This study, based on color Doppler and pulsed Doppler sonographic results of 13 cases with gallbladder carcinoma, eight cases of adenomyomatosis, and eight cases of tumefactive biliary sludge, shows that the presence or absence of blood flow signals helps in the differentiation between gallbladder carcinoma and tumefactive biliary sludge (84.6% sensitivity and 80.0% specificity). However, color Doppler sonography is still not fully capable of distinguishing all gallbladder carcinoma, and a further increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…He also proposed that benign tumors have a lower percentage of detectable blood flow compared with malignant tumors, as an additional differentiation criterion between them. Measurement of the flow rate is also important, with a higher rate for malignant than benign tumors [37]. Hayakawa et al [40] obtained a sensitivity of 0 and specificity of 0.96 for diagnosis of malignant tumor using a cutoff point of 30 cm/s.…”
Section: Ultrasound In Gbcmentioning
confidence: 98%
See 1 more Smart Citation
“…He also proposed that benign tumors have a lower percentage of detectable blood flow compared with malignant tumors, as an additional differentiation criterion between them. Measurement of the flow rate is also important, with a higher rate for malignant than benign tumors [37]. Hayakawa et al [40] obtained a sensitivity of 0 and specificity of 0.96 for diagnosis of malignant tumor using a cutoff point of 30 cm/s.…”
Section: Ultrasound In Gbcmentioning
confidence: 98%
“…Several publications [37][38][39] have underlined its utility in the differential diagnosis of carcinoma with other benign inflammatory or polypoid lesions and with tumescent biliary sludge. Komatsuda et al [37] suggested that detection of flow within the lesion supports the diagnosis of carcinoma versus biliary sludge (Se: 0.84; Sp: 0.80). However, the absence of flow does not completely rule out a tumor.…”
Section: Ultrasound In Gbcmentioning
confidence: 99%
“…A high flow rate of 30 cm/s had a sensitivity of 96%, while a cut off of 20 cm/s had a sensitivity of 72% and specificity of 66% to identify GBC. 20,21 Using EUS, the independent predictors of neoplastic polyps were larger polyp size, larger diameter, height/width ratio of <0.8, presence of heterogenous internal echo pattern, and absence of hyperechoic spotting on EUS were independent predictors for the presence of a neoplastic polyp. A composite EUS score of >12 based on maximum diameter in millimetres, internal echo pattern score and hyperechoic spot had a sensitivity, specificity, and accuracy for the risk of neoplastic polyps of 78%, 83% and 83% respectively.…”
mentioning
confidence: 99%
“…The presence of increased vascularity within a gallbladder polyp suggests malignancy [11,12]. However, the presence of increased vascularity within the gallbladder wall has not been evaluated on power Doppler evaluation to differentiate between malignancy and chronic cholecystitis.…”
Section: Discussionmentioning
confidence: 99%